Mitigating neurodegenerative diseases: the protective influence of baicalin and baicalein through neuroinflammation regulation - Yang, Rui; Wang, Ranran; Xu, Ajing; Zhang, Jian; Ma, Jing (Frontiers in Pharmacology, 2024)
Neurodegenerative diseases (NDDs) represent a category of serious illnesses characterized by the progressive deterioration of neuronal structure and function. The exploration of natural compounds as potential therapeutic agents has gained increasing attention in recent years owing to their wide range of pharmacological activities and minimal side effects. Baicalin (BAI) and baicalein (BE), belonging to the polyphenolic flavonoids, derived from the root of Scutellaria baicalensis, evidently show promise in treating NDDs. This review aimed to provide an overview of the current understanding of the roles of BAI and BE in alleviating neuroinflammation, a pivotal pathological process implicated in various NDDs. Studies conducted prior to clinical trials have shown that BAI and BE exert protective effects on the nervous system in different animal models of NDDs. Furthermore, mechanistic studies indicate that BAI and BE exert their anti-inflammatory effects through inhibiting pro-inflammatory cytokines, suppressing microglial activation and regulating microglial phenotype. These effects are mediated through the modulation of inflammatory signaling cascades, including toll-like receptor 4 (TLR4), mitogenactivated protein kinase (MAPK), amp-activated protein kinase (AMPK), NOD-like receptor thermal protein domain associated protein 3 (NLRP3)inflammasome, and nuclear factor erythroid 2-related factor 2 (Nrf2)/hemoglobin oxygenase-1 (HO-1). Overall, BAI and BE exhibit promising potential as natural compounds with antiinflammatory properties and offer innovative therapeutic approaches for managing NDDs.